LITERASI BUDAYA DI MUSEUM BALI BAGI PELAJAR SMP MELALUI PERLOMBAAN STORYTELLING “MEN BRAYUT” - Pradnya Dewi, Putu; Aliffiati, Aliffiati; Bagus Oka Wedasantara, Ida (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
This research aims to find out the development of cultural literacy at the Bali Museum for junior high school students in Denpasar City through a storytelling competition with the theme